On p-Laplace Equations with Singular Nonlinearities and Critical Sobolev Exponent. (5th September 2022) - El Mokhtar, Mohammed El Mokhtar ould
Abstract : In this paper, we deal with p -Laplace equations with singular nonlinearities and critical Sobolev exponent. By using the Nehari manifold, Mountain Pass theorem, and Maximum principle theorem, we prove the existence of at least four distinct nontrivial solutions.